684 Coach communication about concussion safety and their perceived ability to assess and manage concussion. (1st September 2016) - Sullivan, Lindsay; Molcho, Michal
Abstract : Background: Annually, it is estimated that 3.8 million sports- and recreation-related concussions are sustained in the USA alone, with a particularly high incidence among adolescents. At youth sporting events, however, medical professionals are rarely present. Accordingly, coaches play a crucial role in recognising the signs and symptoms of concussion, and ensuring that players with a suspected concussion are managed correctly. Coaches have also been found to play a central role in reinforcing or undermining a sport culture in which athletes report injuries, including concussion. The aim of this study was to assess perceived ability to assess and manage concussion; and to explore, coaches' communication practices about concussion safety with their players. Methods: Using a self-report questionnaire data were captured on coaches' communication practices about concussion safety and perceived ability to assess and manage concussion among their athletes. Data was collected electronically from June-September 2015. Results were analysed using SPSS Version 22. Results: The final sample consisted of 106 coaches (59 male, 37 female) from the island of Ireland. Results showed that a majority of coaches did not feel equipped to promote concussion education among their athletes (76.5%), determine if a player has sustained a concussion (69.7%) or to help an athlete who obtained a suspected concussion during training or a match (62.6%). Additionally, before the season, a majority of coaches did not talk to their athletes about concussion safety and the importance of concussion reporting. Conclusions: Findings from this study suggest that interventions should encourage communication about concussion safety with athletes and should provide coaches with communication skills and strategies about how to do this. Additionally, coach targeted interventions should focus on instructing coaches on how to recognise and manage a suspected concussion in one of their athletes.